Equisetum - Rovaniemi, Finland - Photograph ... - Campbell, Sandy (University of Alberta Library, 2011)
This horsetail plant was growing in the back yard of an inn in Rovaniemi. It was 47cm from ground to tip. Equisetum or horsetail is a spore producing vascular plant. Members of this genus are abundant around the world and the family is widely represented in the fossil record. ...